Bacterial Pneumonias in Immunocompromised Patients - Van de Louw, Andry; Mirouse, Adrien; Peyrony, Olivier; Lemiale, Virginie; Azoulay, Elie (Seminars in Respiratory and Critical Care Medicine, 2019)
With the overall improvement in survival of cancer patients and the widespread use of novel immunotherapy drugs for malignant as well as nonmalignant diseases, the prevalence of immunosuppression is rising in the population. Immunocompromised patients are particularly exposed to pulmonary infections which remain a leading cause for acute hypoxic respiratory failure and intensive care unit admission. Although fungal or opportunistic infections are always a concern, bacterial pneumonia remains the most common cause of pulmonary infection, is associated with a significant mortality, and has some specificity in this population. Adequate and timely prevention, diagnosis, and management of bacterial pneumonias require knowledge about the complex interplay between host factors (type and severity of immunosuppression) and bacterial pathogenesis, to improve the outcome. We provide an overview of bacterial pneumonias in immunocompromised patients including their epidemiology, risk factors with respect to the pattern of immunosuppression, microbiological characteristics, diagnostic approach, management, and prevention.
Keywords: pneumonia; immunosuppression; cancer; bacteria; acute respiratory failure